Language learning strategies preferred by extrovert and introvert students in English as a second language - Tharani, Sockalingam (2023)
The purpose of this study is to investigate the correlation between personality, extroversion-introversion, and learning second languages behaviours among students. This study also intends to discover the preferred second language learning techniques of extrovert and introvert students. Purposive sampling was used to reach out to 94 students. The study implemented Google Form to generate three types of surveys in order to accomplish the project targets: general demographic information, the McCroskey's Introversion Scale, and the Strategy Inventory for Second Language Learning (SILL, version 7.0). The results of the analysis were analysed using Microsoft Excel and the Statistical Package for the Social Sciences (SPSS, version 26) software. This study investigation found a correlation between personality and learning a second language behaviours. Furthermore, the results indicate that introverted utilised more metacognitive strategies when understanding English, while extroverts utilised more social strategies, and introverted students used more strategies than extroverted students. This information will motivate educators to help pupils embrace suitable approaches for productive language learning